A Call to Action Against Persistent Lack of Transparency in Vaccine Pricing Practices During the COVID-19 Pandemic - Gabriela Arguedas-Ramírez (Ubiquity Press, 2022)
Lack of transparency in vaccine pricing practices is a problem that has been under discussion for a long time. To tackle this, the World Health Assembly adopted the resolution 'Improving the transparency of markets for medicines, vaccines, and other health products' in 2019. However, despite the appalling effects of the current pandemic and the unequal global distribution of vaccines, the 2019 resolution has not been included as a fundamental pillar in the global health response to COVID-19. Governments and public health agencies have provided public funding to pharmaceutical companies for research and development of new vaccines. Yet, information on pricing strategies and methodologies is still inaccessible. Furthermore, these companies are profiting from publicly funded research and development. But secrecy and opacity prevails in the pharmaceutical industry, affecting low and middle income countries. Situating the demand for transparency, accountability and fair pricing of pharmaceutical products as a global health justice issue, I suggest an independent global observatory for accountability and transparency in the pharmaceutical global market should be created to help international organizations, governments and civil society in their quest for affordable and safe vaccines and therapeutics.